Understanding rplD Gene Mutations of Rhodothermus marinus through Mutagenesis using Thermus thermophilus - Silvia, Sophie (DigitalCommons@URI, 2020)
Rhodothermus marinus is a thermohalophilic bacterium isolated from submarine hot springs off the Reykjanes Peninsula in the Isafjardardjup Bay, Iceland. This bacterium has the ability to undergo cellular processes in conditions of extreme heat and high sodium concentrations, such as those present in its native habitat. Phylogenetically, R. marinus is more closely related to mesophiles, raising questions about its ability to adapt and survive in high temperatures. In order to begin the process of developing a model system to study the structure, function, and evolution of the R. marinus ribosome, spontaneous mutants arising when exposed to selective pressures, like antibiotics, need to be isolated. By comparing specific areas of interest in the ribosome, like the peptidyltransferase center (PTC) of 23s rRNA, and ribosomal proteins like uL4, we can identify mutations that allow survival despite potential effects on growth. The PTC has one of the most highly conserved genetic sequences and is resilient to mutation, which are characteristics that contribute to preserving ribosome function which is critical for cell survival. Ribosomal protein uL4 is near the macrolide binding site where macrolide antibiotics reside and inhibit protein synthesis. I have identified novel deletion mutations in R. marinus ribosomal protein uL4. These deletions arose as a result of homologous recombination between short, directly repeated sequences in R. marinus rplD, the gene encoding uL4. Using gene synthesis and molecular genetic approaches, I have begun to reconstruct these mutations in the rplD gene of Thermus thermophilus, a model system for structure-function studies of the ribosome. The ultimate goal of this work is to determine the atomic-resolution structures of mutant ribosomes by X-ray crystallography, thereby establishing the mechanism of antibiotic resistance, and the structural effects of these deletion mutations on a critical ribosome active site.